Labindalawang masasayang prinsesa = Twelve merry princesses - Bellen, Christine S. 1973-; Reyes, Severino 1861-1942 (Bellen, Christine S. Ang mga kuwento ni Lola Basyang ni Severino Reyes, 2011)
A king tries to find worthy husbands for his twelve daughters